2010
DOI: 10.1093/jxb/erq051
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of the genes encoding  6-desaturase from Ribes nigrum 

Abstract: Gamma-linolenic acid (γ-linolenic acid, GLA; C18:3 Δ6, 9, 12) belongs to the omega-6 family and exists primarily in several plant oils, such as evening primrose oil, blackcurrant oil, and borage oil. Δ6-desaturase is a key enzyme involved in the synthesis of GLA. There have been no previous reports on the genes encoding Δ6-desaturase in blackcurrant (Ribes nigrum L.). In this research, five nearly identical copies of Δ6-desaturase gene-like sequences, named RnD8A, RnD8B, RnD6C, RnD6D, and RnD6E, were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Genes encoding plant D 8 -sphingolipid desaturases have been identified from Arabidopsis thaliana, Brassica napus, Helianthus annuus, Borago officinalis, Aquilegia vulgaris, Nicotiana tabacum, Stylosanthes hamata and Ribes nigrum (Sperling et al, 1998(Sperling et al, , 2000(Sperling et al, , 2001Michaelson et al, 2002;García-Maroto et al, 2007;Ryan et al, 2007;Song et al, 2010;Moreno-Pérez et al, 2011). Expression of these cDNA sequences in vivo using S. cerevisiae as a heterologous host resulted in the biosynthesis of both cis-and trans-isomers of plant characteristic 4-hydroxysphing-8-enines, which do not present in wild-type yeast cells (Sperling and Heinz, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Genes encoding plant D 8 -sphingolipid desaturases have been identified from Arabidopsis thaliana, Brassica napus, Helianthus annuus, Borago officinalis, Aquilegia vulgaris, Nicotiana tabacum, Stylosanthes hamata and Ribes nigrum (Sperling et al, 1998(Sperling et al, , 2000(Sperling et al, , 2001Michaelson et al, 2002;García-Maroto et al, 2007;Ryan et al, 2007;Song et al, 2010;Moreno-Pérez et al, 2011). Expression of these cDNA sequences in vivo using S. cerevisiae as a heterologous host resulted in the biosynthesis of both cis-and trans-isomers of plant characteristic 4-hydroxysphing-8-enines, which do not present in wild-type yeast cells (Sperling and Heinz, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although routine analysis of fatty acid methyl esters by GC is reliable, there are variants of ⌬6-like proteins with alternate activities (26). In addition, when a Tetrahymena cytochrome b 5 was coexpressed with Des6, high desaturase activity produced two uncharacterized minor peaks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1), as reported for other front-end desaturases. 6,13) The glutamine residue of the third histidine box, QXXHH, might be very important to maintenance of the proper structure and functioning of desaturases, because the conversion of this residue to histidine and to isoleucine resulted in a loss of enzyme activity. 26) Random mutagenesis of the Á6-desaturase gene from Echium plantagineum indicated that the L14P mutation in cytochrome b 5 and the S301P mutation between histidine box II and histidine box III significantly reduced enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…Two of them were expressed in all tissues at low levels, while the other was expressed only in the seeds. 13) Plant fatty acid desaturases are regulated by various environmental factors. 1) Much research suggests that temperature can regulate fatty acid desaturases at the transcriptional and post-transcriptional levels, as described for FAD2 in several plants, 3,5,33) for FAD6 in olive fruit, 34) for FAD3 in wheat roots, 2) and for FAD8 in Arabidopsis leaves, 35) but no effect of temperature on the expression of the Á6-desaturase gene has been demonstrated in higher plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation